2023
DOI: 10.1007/s13555-023-00926-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Stretch Marks Using a New Formulation Combining Nanofractional Radiofrequency Plus Magnetic Nanofractional Radiofrequency

Abstract: Introduction Stretch marks are common atrophic dermal scars with significant physical and psychological effects. Therefore, there is a need for effective cosmetics and procedures for stretch mark treatment. This study aimed to evaluate the efficacy and safety of a novel treatment for stretch marks that is made up of topical formulations containing beta-glucan combined with nanofractional radiofrequency. Methods This randomized, blinded control trial enrolled 64 Chinese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(63 reference statements)
0
0
0
Order By: Relevance
“…Before starting the treatment series, each patient's striae width, collagen density, skin thickness, and skin color were measured. The research showed that the best results were observed in group C, where the synergy of the nanoFRF treatment and the preparation with β‐glucan was used 24 …”
Section: Cosmetological and Aesthetics Treatmentsmentioning
confidence: 99%
“…Before starting the treatment series, each patient's striae width, collagen density, skin thickness, and skin color were measured. The research showed that the best results were observed in group C, where the synergy of the nanoFRF treatment and the preparation with β‐glucan was used 24 …”
Section: Cosmetological and Aesthetics Treatmentsmentioning
confidence: 99%